Paradigma Nikah Hamil dalam Perspektif Sosiologi Hukum Islam dan Maqashid Syariah - Moh Ahsin; Oyo Sunaryo Mukhlas; Beni Ahmad Saebani (CV. ULIL ALBAB CORP, 2025)
The phenomenon of pregnant marriage, which is a marriage that takes place because of pregnancy outside of marriage, is an important issue that involves various legal and social perspectives. KHI article 53 supports the legality of pregnant marriage by establishing specific rules to protect the rights of women and children. The main factors that trigger pregnant marriages include a lack of religious education, the influence of the social environment, and weak family supervision. Adulterous children in KHI Article 186 and MUI only have a nasab relationship with the mother and her family. The Constitutional Court in Decision No. 46/PUU-VIII/2010 stated that adulterous children have a legal relationship with biological fathers if proven through valid evidence. The sociological perspective of Islamic law emphasises the importance of legal responses to social realities, especially pregnant marriages, to maintain social stability and reduce the stigma experienced by women and children. Meanwhile, maqashid sharia emphasises sharia objectives, such as the protection of honour (hifz al-ird), offspring (hifz an-nasl) and soul (hifz al-nafs) as the basis for the permissibility of pregnant marriage to prevent wider negative impacts.